Self-management in the prevention of skin injuries in adults hospitalized in an emergency department (Boletín Semillero de Investigación en Familia, 2024)
Introduction. Worldwide, the incidence of pressure skin injuries or pressure ulcers (PU) is 5.4% per 10,000 patients and the prevalence is 8.4%. These can increase the risk of dying by five times. The objective of this project was to generate behaviors and knowledge in people for the self-management of this condition.  Materials and methods. A self-management intervention was applied in the prevention of skin lesions in hospitalized adults. This was selected from a systematic search of the literature. To measure the change before and after applying the intervention, two instruments were used: Nursing Outcomes Classification (NOC) "Risk control" of 13 indicators and the KPUP instrument of attitudes towards the prevention of PU of 5 constructs in 13 items: competence; priority; impact; responsibility and efficiency. In addition, student-patient interaction was measured with the Jean Watson Caring Nurse-Patient Interactions scale. Results. The NOC: "Risk control" before and after the intervention for each applied session went from 1.5 (SD= ±0.8) to 3.1 (SD=± 0.1) in session 1; in session 2 it went from 2.2 (SD= ±1.0) to 3.7 (SD ±0.7); for session 3 from 3.1 (SD ±1.7), to 4.6 (SD ±1.1) and finally for sessions 4 and 5 it went from 2.8 (SD ±1.0) to 4, 4 (SD ±0.6). Regarding the results of the attitudes towards the prevention of PUs according to the KPUP constructs, the "Priority" construct was the one that obtained the highest compliance in the role of the caregiver, whose items ranged from 95 to 100%, which indicates that the participants perceive that it is important to prevent pressure ulcers, while the "Competition" construct was the one with the lowest compliance, which means that they still do not feel capable of carrying out their own activities. In relation to the student-patient interaction, the item that the participants valued the most was allowing time for questions to be asked in response to concerns.Conclusions. It was possible to promote self-management and attitudes of the participants in the prevention of PU, evidenced in the results of the NOC and attitudes. In addition, the nurse-patient interaction was recognized.
Keywords: Self-Management; Skin Care; Patient Safety; Pressure Ulcer; Adult